Study of Hybrid Problems under Exponential Type Fractional-Order Derivatives - Mohammed S. Abdo; Sahar Ahmed Idris; M. Daher Albalwi; Tomadir Ahmed Idris (Journal of Mathematics)
In this investigation, we develop a theory for the hybrid boundary value problem for fractional differential equations subject to three-point boundary conditions, including the antiperiodic hybrid boundary condition. On suggested problems, the third-order Caputo–Fabrizio derivative is the fractional operator applied. In this regard, the corresponding hybrid fractional integral equation is obtained by the Caputo–Fabrizio operator’s properties with the Green function’s aid. Then, we apply Dhage’s nonlinear alternative to the Schaefer type to prove the existence results. Finally, two examples are provided to confirm the validity of our main results.